REHABILITATION ACTIVITY OF FAMILIES AS AN EFFICIENCY CRITERION OF THE MEDICAL AND SOCIAL ASSISTANCE TO THE DISABLED CHILDREN - S.A. Kosova; A.A. Modestov; L.S. Namazova (Педиатрическая фармакология)
Rehabilitation of the physically handicapped children requires interdepartmental integration. The most concerned link carrying on the interdepartmental integration may prove to be the family of a disabled child. The parents should have an opportunity and incentives to acquire specific skills to bring up a child and take care of them, since the rehabilitation of the physically handicapped children is a lengthy process and has some distinctive peculiarities at various age stages.Key words: rehabilitation, disabled children.